Autologous concentrated bone marrow injection for precollapse osteonecrosis of the femoral head concurrent with contralateral total hip arthroplasty: protocol for a clinical trial - Muneaki Ishijima; Ken Yamaji; Naoto Tamura; Naotake Yanagisawa; Hiroshi Ohtsu; Takuma Yamasaki; Yasuhiro Homma; Ken Tashiro; Yoshiki Okada; Yuichi Shirogane; Taiji Watari; Koju Hayashi; et al. (BMJ Open, 2024)
Introduction The femoral head contralateral to the collapsed femoral head requiring total hip arthroplasty (THA) often manifests in the precollapse stage of osteonecrosis of the femoral head (ONFH). It is not yet demonstrated how autologous concentrated bone marrow injection may prevent collapse of the femoral head concurrent with contralateral THA. The primary objective is to evaluate the efficacy of autologous concentrated bone marrow injection for the contralateral, non-collapsed, femoral head in patients with bilateral ONFH, with the ipsilateral collapsed femoral head undergoing THA.Methods and analysis This is a multicentre, prospective, non-randomised, historical-data controlled study. We will recruit patients with ONFH who are scheduled for THA and possess a non-collapsed contralateral femoral head. Autologous bone marrow will be collected using a point-of-care device. After concentration, the bone marrow will be injected into the non-collapsed femoral head following the completion of THA in the contralateral hip. The primary outcome is the percentage of femoral head collapse evaluated by an independent data monitoring committee using plain X-rays in two directions 2 years after autologous concentrated bone marrow injection. Postinjection safety, adverse events, pain and hip function will also be assessed. The patients will be evaluated preoperatively, and at 6 months, 1 year and 2 years postoperatively.Ethics and dissemination This protocol has been approved by the Certified Committee for Regenerative Medicine of Tokyo Medical and Dental University and Japan’s Ministry of Healthy, Labour and Welfare and will be performed as a class III regenerative medicine protocol, in accordance with Japan’s Act on the Safety of Regenerative Medicine. The results of this study will be submitted to a peer-review journal for publication. The results of this study are expected to provide evidence to support the inclusion of autologous concentrated bone marrow injections in the non-collapsed femoral head in Japan’s national insurance coverage.Trial registration number jRCTc032200229.